2009
DOI: 10.1007/s12111-009-9096-3
|View full text |Cite
|
Sign up to set email alerts
|

‘Keeping the Faith’: How Incarcerated African American Mothers Use Religion and Spirituality to Cope with Imprisonment

Abstract: Previous studies investigate whether religion aids in rehabilitation and acclimation to the prison structure among the incarcerated. However, few studies investigate whether and how religion and spirituality can assist incarcerated persons as they attempt to cope with the strains of fulfilling family roles while behind bars. Neither does previous prison research adequately investigate the intersections of race, gender, religion, spirituality and mothering. The present study is based on focus groups with fiftee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(52 reference statements)
0
15
0
1
Order By: Relevance
“…La mayoría de los estudios existentes considera indicadores de religiosidad (como participación en programas de corte religioso) en detrimento de la espiritualidad (Clear et al, 2000;Rioux, 2007). Más aún, los estudios existentes fallan en incluso examinar en profundidad otros aspectos más profundos de la religiosidad, no yendo mucho más allá de indicadores como participación en servicios religiosos o haber atendido a programas de este tipo en la prisión (Stringer, 2009).…”
Section: Dificultades Metodológicasunclassified
“…La mayoría de los estudios existentes considera indicadores de religiosidad (como participación en programas de corte religioso) en detrimento de la espiritualidad (Clear et al, 2000;Rioux, 2007). Más aún, los estudios existentes fallan en incluso examinar en profundidad otros aspectos más profundos de la religiosidad, no yendo mucho más allá de indicadores como participación en servicios religiosos o haber atendido a programas de este tipo en la prisión (Stringer, 2009).…”
Section: Dificultades Metodológicasunclassified
“…Cultural and class differences often necessitate that women of color and poor women construct mothering roles that diverge from conventional models (Glenn, 1994). For example, a qualitative study of imprisoned African American mothers found that family values rooted in African traditions and African American culture can positively affect imprisoned women's coping and mothering strategies (Stringer, 2009). Under these conditions biological mothers, relatives, and nonbiological kin may assist with childrearing without altering the identity of an engaged biological mother (Billingsley, 1992).…”
Section: Imprisonment and Factors That Influence Mothering Attitudesmentioning
confidence: 99%
“…Under these conditions biological mothers, relatives, and nonbiological kin may assist with childrearing without altering the identity of an engaged biological mother (Billingsley, 1992). For example, a qualitative study of imprisoned African American mothers found that family values rooted in African traditions and African American culture can positively affect imprisoned women's coping and mothering strategies (Stringer, 2009). Because these cultural features may buffer the negative effect of imprisonment on Black women's maternal identity, we tested for race effects in the current study.…”
Section: Imprisonment and Factors That Influence Mothering Attitudesmentioning
confidence: 99%
“…In a review of research on mental health and religion during imprisonment, 65 Eytan (2011) reported that religious beliefs were associated with lower levels of violence, fewer arguments and disciplinary sanctions. Stringer (2009) postulated that religion helped imprisoned mothers to cope with separation from their children, whilst a study in a Canadian secure forensic-psychiatric centre indicated that religious individuals had lower levels of depression and anxiety, and higher levels of satisfaction with life (Mela 70 et al, 2008). Alternatively, other studies have delineated the potentially criminogenic effects of religion in contributing to distorted thinking which may serve to facilitate the commission of violence, whilst inhibiting responsibility-taking by offenders (Knabb, Welsh, & Graham-Howard, 2012).…”
Section: Introductionmentioning
confidence: 99%